New tirucallane triterpenoids from the dried latex of Euphorbia resinifera. (February 2019) - Wang, Shu-Yun; Huang, Chao; Sun, Ren-Kuan; Lu, Li-Na; Liang, Hong-Gang; Gao, Le; Huang, Jian; Wang, Jin-Hui; Yang, Bao-Feng
Graphical abstract: Highlights: A new triterpene with spiro [5, 6] ring system has been isolated from Euphorbium. The absolute configuration of the compound was confirmed by CD and ECD. Its cytotoxicity against MCF-7, U937 and C6 cancer cell lines was evaluated. Abstract: As a part of our ongoing search for bioactive compounds from the dried latex of Euphorbia resinifera (Euphorbium), a new rearranged tirucallane triterpene with a spiro [5, 6] ring system, euphorol K (1 ), and a novel euphane triterpene hydroperoxide, euphorol J (2 ), together with a known compound, kansuinone (3 ) have been isolated. Their structures were established on the basis of extensive analyses of their spectroscopic, circular dichroism (CD) measurement and theoretical calculation (ECD) methods. The cytotoxicity of all compounds against MCF-7, U937 and C6 cancer cell lines was evaluated. Compounds1 −3 exhibited various degrees of cytotoxic effect against MCF-7.